Associations between medication use and phthalate metabolites in urine and follicular fluid among women undergoing in vitro fertilization - Yao, Yang-Cheng; Liu, Chong; Wu, Lin-Jing; Yuan, Xiao-Qiong; Du, Yao-Yao; Li, Ni-Jie; Guo, Na; Deng, Tao-Ran; Hua, Xiang; Teng, Xue-Mei; Yin, Li; Li, Yu-Feng (Ecotoxicology and environmental safety, 2021)
Phthalates, which are used as excipients of drugs, have been related to adverse reproductive outcomes. However, the relationships between medication use and phthalate exposure among women undergoing in vitro fertilization (IVF) have not been studied. To investigate the associations between the medication intake and phthalate metabolites in urine and follicular fluid (FF). Eight phthalate metabolites were measured in urine and FF samples from 274 women undergoing IVF using liquid chromatography-tandem mass spectrometry. Information on recent medication intake was obtained via interview by trained staff. We constructed generalized linear regression models to examine the associations of medication intake with phthalate metabolite concentrations and dose-response relationships between the number of medicines used and metabolite concentrations in two matrices. Four of 10 drugs were used by more than 10% of the participants, including vitamins (23.0%), traditional Chinese medicine (TCM, 22.3%), antioxidants (12.4%) and amoxicillin (10.2%). Participants who had used TCM had 26.0% (95% CI: 0.0, 58.8%), 32.6% (95% CI: 4.2, 68.8%) and 32.3% (95% CI: 2.6, 70.6%) higher urinary mono-n-butyl phthalate (MBP), mono(2-ethyl-5-hydroxyhexyl) phthalate (MEHHP) and mono(2-ethyl-5-oxohexyl) phthalate (MEOHP) concentrations, respectively, than those who had not. Antioxidant intake was associated with a 30.6% (95% CI: −48.5, −6.6%) decrease in the urinary MBP concentration. Compared with non-users, women who reported the use of medicines had 53.2% (95% CI: 2.7, 128.5%) higher concentrations of MMP and a 37.7% (95% CI: −60.7, −1.5%) lower level of MBP in FF, respectively. Our data suggest that the intake of some medications may increase phthalate exposure among women undergoing IVF. [Display omitted] •Phthalate metabolites were highly detected in urine and follicular fluid of IVF women.•Various medicines are used during infertility treatment.•Traditional Chinese medicine use was positively associated with urinary MBP, MEHHP and MEOHP.•Medication use was positively associated with follicular fluid MMP.